Peningkatan Kemampuan Disposisi Matematika Melalui Pembelajaran Berbasis Persepsi Masyarakat - Maya Nurfitriyanti (SAP (Susunan Artikel Pendidikan), 2017)
This research aims to know the improvement in students’ mathematical disposition skill after performing student’s activity-based learning. The research is a quantitative research with a comparative approach. The statistical test used is t-test. The sample of this research consists of 70 students selected by employing a random sampling technique. Every sample is then similarly treated with two tests. First test or pretest is given before the samples are taught using a concept of student’s activity-based learning and the second test or posttest is provided after the samples are taught using a concept of student’s activity-based learning. The result of the research shows the improvement in students’ mathematical disposition skill after performing student’s activity-based learning. It is as proven in the t-test result, in which tobserved > ttable, namely 14.41 > 1.67 with significant level of 5%.